Penegakan Hukum oleh Aparat Lembaga Pemasyarakatan dalam Menanggulangi Penyelundupan Narkotika - Charles Ferguson Lagaribu De Ornay; I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Warmadewa Press, 2022)
A criminal act is a form of violation of the norms contained in the law and is considered a criminal penalty. The law becomes a social control for the community, so as not to commit acts that deviate from the provisions of positive law in Indonesia which have been regulated in the law. The rule of law is a society with a life regulated by law that must be obeyed and obeyed by the community and its law enforcement officers. The purpose of this study is to understand the Forms of Law Enforcement by Correctional Apparatuses in Overcoming Narcotics Smuggling in Prisons and to analyze the Barriers of Correctional Apparatuses in Overcoming Narcotics Smuggling in Prisons. This research was conducted using a normative research type. Regulations on Narcotics can be seen in Law Number 35 of 2009 concerning Narcotics and Law Number 12 of 1995 concerning Corrections. Narcotics regulation is made as a form of effort in the field of criminal law from the government, especially in terms of eradicating narcotics crimes and preventing narcotics smuggling in Indonesia.